High initial energy finite time blowup with upper bound of blowup time of solution to semilinear parabolic equations. (July 2020) - Ma, He; Meng, Fanmo; Wang, Xingchang
Abstract: A sufficient condition on initial profile ensuring high initial energy finite time blowup along with the upper bound of the corresponding blowup time for the classical semilinear parabolic equations involving initial boundary value problem is established in this paper.